2015
DOI: 10.1002/nau.22752
|View full text |Cite
|
Sign up to set email alerts
|

Use of clean intermittent self‐catheterization in France: A survey of patient and GP perspectives

Abstract: ISC seems to be significant in French general practice whereas practical skills remain heterogeneous. UI, UTI, and constipation are recurrent issues among ISC performers that significantly decrease their quality of life. Education and adapted guidelines for GP guidance could improve these patients' conditions. Neurourol. Urodynam. 35:528-534, 2016. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
3
9
0
1
Order By: Relevance
“…Among the most relevant results of this study were that the profile of people requiring IBC varied greatly in sociodemographic and clinical characteristics, with neurological damage as the reason for prescription in one in three patients. This variability in the prescriptions and characteristics of patients requiring IBC can also be seen in other works [20,21].…”
Section: Discussionsupporting
confidence: 71%
“…Among the most relevant results of this study were that the profile of people requiring IBC varied greatly in sociodemographic and clinical characteristics, with neurological damage as the reason for prescription in one in three patients. This variability in the prescriptions and characteristics of patients requiring IBC can also be seen in other works [20,21].…”
Section: Discussionsupporting
confidence: 71%
“…Assuming a use of four catheters per person per day, 9 these data imply a prevalence of 74 people who use catheters per 100 000 people, which is similar to the prevalence observed in France (62 users per 100 000 people). 10 Although precise data are unavailable, the prevalence of repeated UTIs that is associated with CISC use is likely to be similar in other countries with sufficient health-care resources.…”
Section: Introductionmentioning
confidence: 99%
“…The year with the highest number of published articles was 2011 with three studies (16)(17)(18) , followed by 2002 and 2015 (19)(20)(21)(22) , both with two studies each. It should be noted that the earliest study that addresses the theme dates back to 1990 (23) , and the most recent is from 2016 (24) .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the language, nine articles (16)(17)19,(21)(22)(24)(25)(26)(27) were published in English, and four in Portuguese (18,20,23,28) . In relation to the databases, five were identified in the MEDLINE/ PubMed (21,(24)(25)(26)(27) , five in the LILACS (17)(18)20,23,28) , two in the CINAHL (16,19) and one in the SCOPUS (22) . It should be noted that the four studies identified in Portuguese were carried out in Brazil.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation